Analysis of Anaerobic Capacity of Basketball Athletes in the Provincial Championship of Balangan Regency (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This research aims to analyze the anaerobic capacity of basketball athletes from the Regional Championship of Balangan Regency to provide an overview of the athletes' physical condition and recommendations for training program development. The method used is a quantitative descriptive study with purposive sampling techniques, involving 16 athletes who meet the criteria as samples. The measurement instrument used is the Running-based Anaerobic Sprint Test (RAST) based on a validated Android application. The collected data includes maximum power, minimum power, average power, and fatigue index, which are then categorized based on physical fitness norms. The results show that out of 16 athletes tested, 12 athletes (75%) have anaerobic endurance in the 'very good' category, and 4 athletes (25%) are in the 'good' category. No athletes were found in the moderate, insufficient, or very insufficient categories. The maximum average power obtained is 222.89, the minimum power is 122.71, and the average power is 165.22. This study concludes that the anaerobic capacity of basketball athletes in the Balangan District provincial championship is generally very good. However, there is still room for improvement, particularly in recovery efficiency after intense activities. The results of this study are expected to serve as a reference for coaches in designing more directed training programs to improve athletes' performance, especially in the aspect of anaerobic endurance.